Break into left anterior descending coronary artery suggest myocardial bridging - Siniscalchi, Carmine; Basaglia, Manuela; Gaibazzi, Nicola (Acta Biomedica Atenei Parmensis, 2016)
A 67 year-old woman presented with stable effort angina. A resting electrocardiogram was inconclusive. High-dose dipyridamole contrast-echocardiography shows normal left ventricular wall motion after 0.84mg/kg/6min dipyridamole. At rest a turbolent flow demonstrable by color aliasing, appeared in the territory of the left anterior descending coronary artery (LAD) during the diastolic phase.